Steering the climate system: using inertia to lower the cost of policy: comment - Mattauch, L; Matthews, HD; Millar, R; Rezai, A; Solomon, S; Venmans, F (American Economic Association, 2020)
Lemoine and Rudik (2017) argues that it is efficient to delay reducing carbon emissions, due to supposed inertia in the climate system's response to emissions. This conclusion rests upon misunderstanding the relevant earth system modeling: there is no substantial lag between CO2 emissions and warming. Applying a representation of the earth system that captures the range of responses seen in complex earth system models invalidates the original article's implications for climate policy. The least-cost policy path that limits warming to 2°C implies that the carbon price starts high and increases at the interest rate. It cannot rely on climate inertia to delay reducing and allow greater cumulative emissions.